2022
DOI: 10.1155/2022/5847175
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence and Correlation of Metabolic Syndrome in Patients with Bipolar Disorder in NGHA, Riyadh

Abstract: Background. Metabolic syndrome is considered dangerous, especially to patients that are diagnosed with a mental condition such as bipolar disorder, since these types of patients can be difficult to deal with. Metabolic syndrome can lead to multiple cardiovascular diseases, strokes, and diabetes. A careful approach is important when it comes to facing a complex condition such as this. This research will contribute to giving more information about the prevalence and statistics of metabolic syndrome in bipolar di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%